Optimasi Pemanfaatan Lahan Pada Proyek Pengembangan Perumahan Dengan Metode Simpleks - Monika Natalia -; Etri Etri Suhelmidawati -; Afrilia Handayani Yuzar (Jurnal Ilmiah Poli Rekayasa, 2020)
House is one of primary human needs. Realizing the importance of housing needs, developers take advantage of these opportunities to provide recidential house. The main problem that often happens in housing development is difficulty in determining proportion of the types of houses that will be built within the size of land owned. To obtain the optimum amount of each type of house that will be built with the limits available, then set up a model. The optimization calculate is using the simplex method. The constraints for housing development consist of land area for each type of house with the total land area allocated for buildings is 16.116m2; The time available to complete the building is 364 days; Cost budget allocated for the development is Rp. 80.000.000.000,00 and comparison of market demand for each house is 10:6:15:5. The analysis result showed that the composition of optimum number of houses to be built are: 44 units of type 36A, 26 units of type 36B, 67 units of type 60 and 23 units of type 107 with maximum profit is Rp. 14.117.171.000,00.